Social movement as a form of online political participation in social media - Azizah, Nur (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Exists the development of technology and communication 4.0 in Indonesia, were there has been a shift in the form of aspirations in the community from a conventional movement to a digital movement that is easily and very quickly disseminated and brings more support from many people. The purpose of this study is to analyze the role of social media activists in mobilizing public participation with social movements and how the digital instrument Twitter can enhance democratic activities in Indonesia. Method used in this paper is literature review. The results indicate that the relationship between the role of digital technology and social movements can be seen from the power of the hashtag #MahasiswaBergerak which activists use to disseminate into an activity called a social movement which occupies the second trending peak. The use of the hashtag #MahasiswaBergerak is a symbol of the message contained in the hashtag. Users who are involved in liking, commenting, sharing, and retweeting using the hashtag #MahasiswaBergerak is a slactivism practice where only by carrying out these digital activities they have shown participation even though they do not have an impact on real change. Social media can become an alternative media in raising social issues to the surface.